Cover Feature: Unconventional Approaches to Hydrogen Sorption Reactions: Non‐Thermal and Non‐Straightforward Thermally Driven Methods (ChemPhysChem 10/2019). Issue 10 (15th May 2019) - Ares, Jose‐Ramón; Nevshupa, Roman; Muñoz‐Cortés, Esmeralda; Sánchez, Carlos; Leardini, Fabrice; Ferrer, Isabel‐J.; Minh Huy Tran, Vo; Aguey‐Zinsou, Francois; Fernández, Jose‐Francisco
Abstract : The Cover Feature illustrates unconventional approaches (electromagnetic radiation, mechanical bias, electrochemistry way, electrical and magnetic fields…) that could be used as energy sources to surmount the thermodynamic and kinetic landscapes on the H2 ‐sorption reactions on hydrides represented by the valleys and mountains in the picture. More information can be found in the Minireview by J.‐R. Ares et al. on page 1248 in Issue 10, 2019 (DOI: 10.1002/cphc.201801182 ).